GIS-Based Analysis of Spatial Distribution of Medicinal and Herbal Plants in Arid and Semi-arid Zones in the North-west of Jordan - Al-Bakri, Jawad Taleb; Al-Eiswi, Dawud; Damhoureyeh, Said; Oran, Sawsan (Annals of Arid Zone, 2016)
This study integrates geographic information systems (GIS) and ground surveys to map medicinal and herbal (MH) plants in a semi-arid and arid Mediterranean area in the north-west of Jordan. GIS layers of land use/cover, slope and aspects were created and different GIS functions were implemented to investigate the relationships between the number of MH plant species and land use types, altitude, slope and aspect. Statistical analysis was carried out to test the significance of the spatial distribution of the total number of plants and plant species among the sampled grids. Data from ground survey and GIS layers were then used to identify hotspots with high potential for conservation of MH plants. Results showed that more than 600 plant species, including 223 MH species, were recorded in the study area. The study area was characterized by intensive agricultural activities and urbanization, which affected spatial distribution of MH plants. The number of MH plant species tended to significantly (P < 0.05, R2 = 0.46) decrease with altitude. The spatial distribution of MH plants was different from one species to another and was different from the distribution of all plant species (MH and non MH plants). Spatial distribution of hotspots, which was affected by different factors, including land use and global importance of MH plant species, recommended different sites for an in-situ conservation of MH plants. The study showed that anthropogenic factors were obviously impacting the spatial distribution of MH plants in this diverse semi-arid and arid area. Key words: GIS, Jordan, arid, semi-arid, medicinal plants, Mediterranean